Exploring Factors Affecting the Emergency Specialists’ Decision-Making in Case of Emergencies in Patients - Abbasali Ebrahimian; Seyed-Hossein Hashemi-Amrei; Mohammadreza Monesan (Critical Care Research and Practice)
Introduction. Appropriate decision-making is essential in emergency situations; however, little information is available on how emergency decision-makers decide on the emergency status of the patients shifted to the emergency department of the hospital. This study aimed at explaining the factors that influence the emergency specialists’ decision-making in case of emergency conditions in patients. Methods. This study was carried out with a qualitative content analysis approach. The participants were selected based on purposive sampling by the emergency specialists. The data were collected through semistructured interviews and were analyzed using the method proposed by Graneheim and Lundman. Results. The core theme of the study was “efforts to perceive the acute health threats of the patient.” This theme was derived from the main classes, including “the identification of the acute threats based on the patient’s condition” and “the identification of the acute threats based on peripheral conditions.” Conclusions. The conditions governing the decision-making process about patients in the emergency department differ from the conditions in other health-care departments at hospitals. Emergency specialists may have several approaches to decide about the patients’ emergency conditions. Therefore, notably, the emergency specialists’ working conditions and the others’ expectations from these specialists should be considered.